The little data book 2008 (The World Bank, 2008)
This new addition to the Little Data Book series presents at-a-glance tables for over 140 economies showing the most recent national data on key indicators of information and communications technology (ICT), including access, quality, affordability, efficiency, sustainability, and applications.